Traffic Anthropology in Operation Ketupat 2025: Social Practices of Cross-Sectoral Collaboration, Officer Discretion, and Traveler Experience on the Island of Java - Bakharuddin Muhammad Syah (Sekolah Tinggi Agama Islam Kuningan, 2026)
Background: Operation Ketupat is an annual national agenda in Indonesia that mobilizes large numbers of travelers and requires intensive cross-institutional coordination. This study investigates the social dynamics, cultural practices, and institutional mechanisms shaping the implementation of Operation Ketupat 2025 through the perspective of police anthropology. Objective: This study aims to explore how work culture, interagency coordination, and traveler behavior influence the effectiveness of the operation, highlighting the socio-institutional processes that support large-scale traffic management during the 2025 Eid exodus. Methods: A qualitative ethnographic approach was employed, including in-depth interviews and participant observation conducted across six provinces on the island of Java (Banten, DKI Jakarta, West Java, Central Java, the Special Region of Yogyakarta, and East Java) during the 2025 Eid exodus and return period. Results: The findings indicate that operational success is shaped by three interrelated dimensions: (1) cross-sectoral collaboration functions as a coordination ritual that builds shared language and institutional trust; (2) field officers exercise discretionary practices and bricolage, improvising solutions amid resource constraints; and (3) travelers act as rational agents by actively navigating traffic regulations, reconstructing safety norms, and demonstrating adaptive capacity. These dimensions reveal that operational effectiveness relies on social relationships and collective adaptation rather than on technology alone. Conclusion: Operation Ketupat 2025 demonstrates that social relationships embedded in institutional coordination are central to operational success. Cross-sectoral collaboration, officer discretion, and traveler agency form an interconnected socio-institutional system. Policy recommendations include strengthening soft-skills training for field officers, formalizing interagency communication protocols, and implementing structured traveler feedback mechanisms to enhance future large-scale traffic operations.